2022
DOI: 10.1186/s12989-022-00491-w
|View full text |Cite
|
Sign up to set email alerts
|

Changes of physico-chemical properties of nano-biomaterials by digestion fluids affect the physiological properties of epithelial intestinal cells and barrier models

Abstract: Background The widespread use of nano-biomaterials (NBMs) has increased the chance of human exposure. Although ingestion is one of the major routes of exposure to NBMs, it is not thoroughly studied to date. NBMs are expected to be dramatically modified following the transit into the oral-gastric-intestinal (OGI) tract. How these transformations affect their interaction with intestinal cells is still poorly understood. NBMs of different chemical nature—lipid-surfactant nanoparticles (LSNPs), car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 140 publications
2
10
0
Order By: Relevance
“…Inhalation is a major route of human exposure to airborne NFs, and it may occur at workplaces, and A549 cells are a well-established line used for inhalation toxicological testing, including AgNFs . Ingestion is another important route of exposure, and with regard to intestinal exposure, ingested NFs pass through various environments before reaching the intestinal cells, such as saliva, gastric, and intestinal fluids. , Due to the complex nature of these fluids such as acidic conditions, the presence of salts and biomolecules, the pchem properties of NFs could be altered before, during, and after passing the gastrointestinal tract, affecting their bioactivity. , To mimic the fate of NFs, simulated digestive fluids were prepared based on ref , and NF preparation in simulated digestion cascade was performed according to ref . Finally, digested and non-digested NFs were exposed to HCT-116 cells, a well-accepted model for testing NF intestinal cytotoxicity …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhalation is a major route of human exposure to airborne NFs, and it may occur at workplaces, and A549 cells are a well-established line used for inhalation toxicological testing, including AgNFs . Ingestion is another important route of exposure, and with regard to intestinal exposure, ingested NFs pass through various environments before reaching the intestinal cells, such as saliva, gastric, and intestinal fluids. , Due to the complex nature of these fluids such as acidic conditions, the presence of salts and biomolecules, the pchem properties of NFs could be altered before, during, and after passing the gastrointestinal tract, affecting their bioactivity. , To mimic the fate of NFs, simulated digestive fluids were prepared based on ref , and NF preparation in simulated digestion cascade was performed according to ref . Finally, digested and non-digested NFs were exposed to HCT-116 cells, a well-accepted model for testing NF intestinal cytotoxicity …”
Section: Methodsmentioning
confidence: 99%
“…49 Ingestion is another important route of exposure, 50 and with regard to intestinal exposure, ingested NFs pass through various environments before reaching the intestinal cells, such as saliva, gastric, and intestinal fluids. 51,52 Due to the complex nature of these fluids such as acidic conditions, the presence of salts and biomolecules, the pchem properties of NFs could be altered before, during, and after passing the gastrointestinal tract, affecting their bioactivity. 53,54 To mimic the fate of NFs, simulated digestive fluids were prepared based on ref 55, and NF preparation in simulated digestion cascade was performed according to ref 56.…”
Section: Data Collectionmentioning
confidence: 99%
“…Concerning the oral route, we previously reported that NPs acquire during the transit in the gastrointestinal tract a protein corona that contains proteases potentially able to modulate the NP crossing and effect on the gastrointestinal barrier since involved in the regulation of the intestinal permeability. 165 To impede the formation of the protein corona and to stabilize the NPs avoiding dissolution, biodegradation or agglomeration, surface modifications are normally applied. PEGylation is the most popular one.…”
Section: Clinical Potential Of Photoresponsive Inorganic Nanomaterial...mentioning
confidence: 99%
“…Studies on NBMs’ toxicity, including Fe 3 O 4 PEG-PLGA, are mostly available for in vitro models, without much information on their effects on environmental species. Several in vitro cytotoxicity studies with Fe 3 O 4 PEG-PLGA indicate an overall low-to-no toxicity to different cell models [ 16 , 17 , 18 ]. Genotoxicity was also not observed in HCT116 cells exposed to Fe 3 O 4 PEG-PLGA up to 50 μg/mL [ 16 , 18 ], despite the increase in reactive oxygen species (ROS) levels observed above 10 μg/mL [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro cytotoxicity studies with Fe 3 O 4 PEG-PLGA indicate an overall low-to-no toxicity to different cell models [ 16 , 17 , 18 ]. Genotoxicity was also not observed in HCT116 cells exposed to Fe 3 O 4 PEG-PLGA up to 50 μg/mL [ 16 , 18 ], despite the increase in reactive oxygen species (ROS) levels observed above 10 μg/mL [ 16 ]. In a study performed in an environmental species, i.e., using the fish cell lines RTL-W1 (CRL-2301, derived from the liver), RTgill-W1 (CRL-2523, derived from the branchial arc), and RTS-11 (derived from the spleen), up to 100 μg/mL within 24 h [ 19 ] of Fe 3 O 4 PEG-PLGA was also not acutely toxic.…”
Section: Introductionmentioning
confidence: 99%